A quantitative study of thermal cycling along the build direction of Ti-6Al-4V produced by laser powder bed fusion. (January 2023) - Chen, Ming; Simonelli, Marco; Van Petegem, Steven; Yau Tse, Yau; Sin Ting Chang, Cynthia; Grazyna Makowska, Malgorzata; Ferreira Sanchez, Dario; Moens-Van Swygenhoven, Helena
Graphical abstract: Highlights: High-speed in situ X-ray diffraction during laser scanning were performed on a Ti-6Al-4V thin wall produced by laser powder bed fusion. The temperature evolution and cooling rates were determined as a function of depth with a time resolution of 50 µs. Based on the evolution of the crystallographic phases the shape of the melt pool and the β phase in the heat-affected zone could be estimated. The depth-dependent temperature profiles provide valuable input for the calibration of finite element simulations. Abstract: During laser-powder bed fusion (l -PBF) the printed material is subjected to multiple fast heating and cooling cycles when the laser interacts with neighboring tracks or layers above. The complex thermal history influences the final microstructure and the macroscopic properties of the printed part. In this work, we demonstrate how high-speed in situ X-ray diffraction in transmission mode can be used to measure temperature profiles and cooling rates in a Ti-6Al-4V single-track wall. During the laser remelting of the top layer, a temperature exceeding the β transus temperature (Tβ  ∼ 1252 K) is measured up to 150 µm below the surface. The maximum observed cooling rates vary from 10 6 K/s at the top surface, to 10 5 K/s at a depth of 135 µm and 10 4 K/s at a depth of 255 µm. Based on the temporal evolution of the various crystallographic phases, the dimensions of the melt pool and the high-temperature β zone surrounding the melt pool are estimated. It is anticipated that the data obtained from in situ measurements in transmission mode on a thin wall combined with in situ measurements in reflection mode on a bulk sample will allow verification and validation of finite element models used in l -PBF processing.